Supreme Court v. Necropolitics: The Chaotic Judicialization of COVID-19 in Brazil - João Biehl; Lucas E. A. Prates; Joseph J. Amon (Harvard FXB Center for Health and Human Rights, 2020)
Worldwide, governments have reacted to the COVID-19 pandemic with emergency orders and policies restricting rights to movement, assembly, and education that have impacted daily lives and livelihoods in profound ways. But some leaders, such as President Jair Bolsonaro in Brazil, have resisted taking such steps, denying the seriousness of the pandemic and sabotaging local control measures, thereby compromising population health. Facing one of the world's highest rates of COVID-19 infections and deaths, multiple political actors in Brazil have resorted to judicialization to advance the right to health and other protections in the country. Responding to this litigation has provided the country's Supreme Court an opportunity to assertively confront and counter the executive's necropolitics. In this article, we probe the malleable form and the constitutional basis of the Supreme Court's decisions, assessing their impact on the separation of powers, on the protection of human rights (for example, on those of prisoners, indigenous peoples, and essential workers), and relative to the implementation of evidence-based interventions (for example, lockdowns and vaccination). While the court's actions open up a distinct legal-political field (sometimes called "supremocracy")-oscillating between progressive imperatives, neoliberal valuations, and conservative decisions-the capacity of the judiciary to significantly address systemic violence and to robustly advance human rights remains to be seen.